Adjunct ketamine treatment effects on treatment-resistant depressive symptoms in chronic treatment-resistant schizophrenia patients are short-term and disassociated from regional homogeneity changes in key brain regions – a pilot study. Issue 4 (2nd October 2019) - Ye, Jiaen; Lin, Xiaodong; Jiang, Deguo; Chen, Min; Zhang, Yanchi; Tian, Hongjun; Li, Jie; Zhuo, Chuanjun; Zhao, Yanling
ABSTRACT: BACKGROUND: To investigate the effects of adjunct ketamine treatment on depressive symptoms and brain activity in chronic treatment-resistant schizophrenia (CTRS) patients with treatment-resistant depressive (TRD) symptoms. METHODS: Calgary Depression Scale for Schizophrenia (CDSS), positive and negative syndrome scale (PANSS), and regional homogeneity (ReHo) results were compared before versus after ketamine treatment in 12 CTRS patients with TRD symptoms. RESULTS: From 7 days to 14 days after the first ketamine administration, CDSS and PANSS total scores were reduced by 63.8% and 12.9%, respectively. By day 21, ReHo values had increased in the main components of the default mode network (DMN) and bilateral orbitofrontal cortex (OFC) after family-wise error correction. ReHo alterations did not correlate with TRD symptom changes. TRD symptoms relapsed by the 21-day time point, while increased ReHo was sustained. No adverse secondary effects (ASEs) necessitating medical intervention occurred. CONCLUSIONS: Adjunct ketamine alleviation of TRD symptoms lasted only a week, whereas increased ReHo in DMN regions and the OFC in CTRS patients was maintained beyond 2 weeks, indicating that adjunct ketamine is not well-suited for CTRS patients with TRD symptoms and that effects on functional activity dissociate from effects on TRD symptoms. This small-sample pilot study provides clues for further research into therapy for TRD symptoms in CTRS patients.